Client satisfaction on contractors' work performance - Adanan, Hadiatul Aida (2006)
Client satisfaction in the construction industry can be defined as how well a contractor meets the client's expectation. A contractor must have a detailed understanding of the customer expectations and be able to satisfy those expectations. The aim of this study is to identify the appropriate criteria in improving the measurement methodology of contractor performance for client satisfaction and continual improvement. The need of the identification criteria of client's satisfaction is to ensure that the contractor and the client are aiming at the same targets and perceptions. The objectives of the study are to identify the constituents of clients' satisfaction, criteria for assessment, and actual levels of satisfaction and performances, as perceived by clients. The study focused on the client satisfaction on contractor work performance in dealing with construction projects by Sunway Construction Sdn. Bhd. The respondents are among middle management level of the clients and consultants who directly involved with the monitoring of project at construction site. The data collected was analyzed using the Average Index methodology and qualitative analysis. The study shows that the very important criteria in assessing contractor work performance are related to the project planning, contract administration, construction, quality and safety. The main concerned of the areas of improvement by clients are staff competency, timely completion, resources supervision and monitoring, quality consciousness and safety compliance. The premise is that when those identified areas are improved, the continuous improvement shall be attained. The improvement of the measurement criteria of client satisfaction shall demonstrate the benefits of achieving client satisfaction which emphasizing on prevention method of do it right the first time to eliminate waste and rework. This turn will lead to an overall improvement of quality, productivity and competitiveness of the construction industry